Settlement of a Full Scale Trial Embankment on Peat in Kalimantan: Field Measurements and Finite Element Simulations - Susila, Endra; Apoji, Dayu (Institut Teknologi Bandung, 2012)
Abstract. This paper presents a study result of peat behaviors through numerical analysis using the finite element method verified by full scale field measurements. Site investigation, construction, instrumentation and monitoring of a trial embankment on very compressible fibrous tropical peat layers at Bereng Bengkel in Central Kalimantan have been conducted by the Agency of Research and Development, the Indonesia Ministry of Public Works. Settlement responses of the embankment have been investigated by a series of finite element simulations using two different soil constitutive models: elastic perfectly plastic model with the Mohr-Coulomb criteria and hyperbolic Hardening-Soil model. A half space finite element model has been developed using the effective stress approach. Analyses were performed with the coupled static/consolidation theory. The soil parameters, embankment geometry, construction sequence and consolidation time of peats and clays were modeled in accordance with actual field trial embankment conditions. Implementation of the numerical model and simulations has completely been performed by a computer program, PLAXIS 2D. For ground settlement behavior at center of embankment, this study result shows that both soil constitutive models have reasonably produced suitable deformation behaviors. However, the settlement behaviors at embankment toes are not as accurate as they are at center. Abstrak. Makalah ini menyajikan studi perilaku gambut melalui analisis numerik berdasarkan metode elemen hingga yang diverifikasi dengan pengukuran lapangan skala penuh. Investigasi lokasi, konstruksi, instrumentasi dan pengukuran timbunan di atas lapisan gambut tropis berserat yang sangat kompresibel di Bereng Bengkel, Kalimantan Tengah, telah dilakukan oleh Departemen Penelitian dan Pengembangan dari Departemen Pekerjaan Umum Indonesia. Respon penurunan timbinan ini telah dianalisis melalui serangkaian simulasi numerik elemen hingga menggunakan dua model konstitutif tanah: model elastis plastis sempurna dengan kriteria keruntuhan Mohr-Coulomb dan model hiperbolik Hardening-Soil. Model elemen hingga setengah ruang telah dibuat dengan pendekatan tegangan efektif. Seluruh tahapan simulasi telah diperhitungkan sebagai analisis statis/konsolidasi couple. Parameter tanah, geometri timbunan, tahapan konstruksi dan waktu konsolidasi gambut dan lempung dimodelkan sesuai dengan kondisi lapangan. Implementasi dari model dan simulasi numerik ini telah dilakukan menggunakan program komputer PLAXIS 2D. Untuk perilaku penurunan tanah di tengah timbunan, studi ini menunjukkan bahwa kedua model konstitutif tanah dapat menghasilkan perilaku deformasi yang cukup sesuai. Namun, prediksi perilaku penurunan tanah di kaki timbunan tidak seakurat prediksi perilaku di tengah timbunan.